Learners’ reception of translanguaging as a model for reading English L2 texts - Mabena, Mampoi Irene (Journal for Language Teaching, 2023)
Language is the mediator of two critical aspects of a child’s education: identity and knowledge. Through language, learners can make sense of who they are and make sense of the world around them. However, the teaching of English second language in several schools in South Africa is such that a learner’s identity, best described in their own indigenous languages, is not mirrored in the classroom and, in its place, a monolingual system (English-only) becomes central. Their acquired linguistic repertoire as multilingual learners is considered a hindrance to learning, not a resource. This paper assesses learners’ reception of translanguaging pedagogy as a model for reading English texts. It further seeks to take the debate about the paradox of translanguaging forward to determine if translanguaging is a unitary, differentiated system, or both. Exploring data in the form of class observations and interviews, the study reveals that translanguaging as a model for reading English L2 texts is well-received by learners as a practical and valuable pedagogical approach that can potentially improve English L2 performance. The results further establish the existence of both the unitary and the differentiated systems of translanguaging. In the end, the study’s recommendations for transforming multilingual classrooms are discussed.